IMPLIKASI KEPEMIMPINAN PENDIDIKAN TERHADAP DINAMIKA KELOMPOK DAN KINERJA TIM KERJA: SYSTEMATIC LITERATURE REVIEW - Tubagus Habibi; Riana; Fuad Abdul Baqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational leadership plays a crucial role in shaping group dynamics and team performance within educational organizations. Schools as professional organizations rely heavily on collective work among teachers, educational staff, and leaders to achieve institutional goals. This study aims to systematically review empirical and conceptual studies examining the implications of educational leadership on group dynamics and team performance. Using a Systematic Literature Review (SLR) approach, this study analyzes peer-reviewed journal articles published between 2021 and 2025 obtained from reputable academic databases. The findings reveal that educational leadership significantly influences team performance through its impact on group dynamics, including trust, psychological safety, collective efficacy, communication, and conflict management. Effective educational leadership fosters collaborative and adaptive team environments, enabling teams to respond constructively to organizational challenges and educational changes. This study highlights that leadership implications on team performance are mediated by social and psychological processes within groups, emphasizing the importance of leadership practices that support collaboration, empowerment, and shared responsibility in educational settings. Keywords: educational leadership, group dynamics, team performance, teamwork, systematic literature review